Geo-polymerized cementitious material as a stabilizer of waste fly ash to produce green building bricks - Tebogo MASHIFANA (Journal of Sustainable Construction Materials and Technologies, 2021)
Fly ash (FA) and granulated blast furnace slag (GBFS) are waste materials that are readily available. The purpose of this study was to develop a cementitious material (CM) through geopolymerization and utilize it with GBFS to stabilized FA to produce sustainable building material. The strength development of CM stabilized FA was studied over the curing periods of 3, 7, 14, 28, 56 and 90 days. The specimens were evaluated for elemental composition, mineralogy, micrography and unconfined compressive strength (UCS). Stabilization of FA with GBFS yielded the highest strength of 0.24 MPa. The CM improved the strength of the specimen significantly and the strength of 8.86 MPa was attained with a mix design containing 50% FA and 50% CM. Curing for longer period up to 90 days improved the strength of the specimen to 16.03 MPa. CM proved to be the best stabilizer for the FA investigated. Stabilization of FA with a CM was successful and based on the strength attained, the specimen produced can be used to make building bricks.